Cult of Chucky [videorecording (DVD)] - Mancini, Don, 1963-; Dourif, Fiona, 1981-; Therriault, Michael; Hurtig, Adam (Universal Pictures Home Entertainment, 2017)
Confined to an asylum for the criminally insane for the past four years, Nica is wrongly convinced that she, not Chucky, murdered her entire family. But when her psychiatrist introduces a new group therapy tool, a "Good Guy" doll, a string of grisly deaths plague the asylum and Nica starts to wonder if maybe she isn't crazy after all. Andy, Chucky's now-grown-up nemesis from the original Child's Play, races to Nica's aid.